The Moderating Role of Genetics: The Effect of Length of Hospitalization on Children’s Internalizing and Externalizing Behaviors - Benish-Weisman, Maya; Kerem, Eitan; Knafo-Noam, Ariel; Belsky, Jay (Frontiers in Psychiatry, 2015)
The study considered individual differences in children's ability to adjust to hospitalization and found the length of hospitalization to be related to serious emotional and behavioral problems for some and to adaptive psychological functioning for others. Applying the theoretical framework of three competing models of gene X environment interactions (diathesis-stress, differential susceptibility and vantage sensitivity), the study examined the moderating effect of genetic (DRD4) on the relationship between the length of hospitalization and internalizing and externalizing problems. Mothers reported on children’s hospitalization background and conduct problems (externalizing) and emotional symptoms (internalizing), using subscales of the 25-item Strength and Difficulties Questionnaire (1). Data on both hospitalization and genetics were available for 65 children, 57% of whom were females, with an average age of 61.4 months (SD=2.3). The study found length of hospitalization did not predict emotional and behavior problems per se, but the interaction with genetics was significant; the length of hospitalization was related to diminished levels of internalizing and externalizing problems only for children with 7R allele (the sensitive variant). The vantage sensitivity model best accounted for how the length of hospitalization and genetics related to children's internalizing and externalizing problems. Longer periods of hospitalization appeared to benefit children with sensitive genetic makeup.